2021
DOI: 10.1177/18479804211001148
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational analysis of nanoplate with surface irregularity via Kirchhoff plate theory

Abstract: In this work, an attempt is done to apply the Kirchhoff plate theory to find out the vibrational analyses of a nanoplate incorporating surface irregularity effects. The effects of surface irregularity on natural frequency of vibration of nanomaterials, especially for nanoplates, have not been investigated before, and most of the previous research have been carried for regular nanoplates. Therefore, it must be emphasized that the vibrations of irregular nanoplate are novel and applicable for the nanodevices, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Additionally, the impact of surface effects on the resonant frequency of Timoshenko nanobeams has been studied, considering shear deformation, rotary inertia effects, and surface effects [24]. Furthermore, the vibrational analysis of nanoplates with surface irregularities has revealed the influence of surface irregularity on the natural frequency of vibration, particularly for nanoplates [25]. Research on the surface effects of anti-plane shear waves in magnetoelectro-elastic nanoplates has indicated that surface parameters strongly affect elastic wave propagation and dispersion properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the impact of surface effects on the resonant frequency of Timoshenko nanobeams has been studied, considering shear deformation, rotary inertia effects, and surface effects [24]. Furthermore, the vibrational analysis of nanoplates with surface irregularities has revealed the influence of surface irregularity on the natural frequency of vibration, particularly for nanoplates [25]. Research on the surface effects of anti-plane shear waves in magnetoelectro-elastic nanoplates has indicated that surface parameters strongly affect elastic wave propagation and dispersion properties [26].…”
Section: Introductionmentioning
confidence: 99%